The new book about the cossack historian general I.D. Popco [Review: Trekhbratov B. A. The fate of the Kuban officer in the context of the general history of the region. Krasnodar: Tradition publ., 2021. 208 p., ill. ISBN 978- 5-91883-395-7: 300 copies.] - T. A. Kolosovskaya (Гуманитарные и юридические исследования)
.